Reduced Thalamic Volume and Metabolites in Type 1 Diabetes with Polyneuropathy - Hansen, Tine M.; Frøkjær, Jens B.; Selvarajah, Dinesh; Muthulingam, Janusiya A.; Tesfaye, Solomon; Juhl, Anne; Drewes, Asbjørn M.; Jakobsen, Poul E.; Karmisholt, Jesper; Brock, Birgitte; Brock, Christina (Experimental and Clinical Endocrinology & Diabetes, 2021)
Objective Thalamus is essential in processing of sensory information. This study explored the associations between thalamic volume and intra-thalamic metabolites and associations to clinical and experimental characteristics of sensory function in adults with diabetic polyneuropathy.Methods 48 adults with type 1 diabetes and confirmed distal symmetric peripheral neuropathy (DPSN) and 28 healthy controls participated in a cross-sectional study and underwent a brain magnetic resonance imaging scan. Estimates for thalamic volume were extracted using voxel-based morphometry and intra-thalamic N-acetylaspartate/creatine (NAA/cre) levels were assessed by magnetic resonance spectroscopy. Associations between thalamic volume and clinical measures, quantitative sensory testing and neuropathic phenotype were explored.Results In diabetes, reduced gray matter volume was identified including bilateral thalamus (all p≤0.001) in comparison to healthy participants. Thalamic volume estimates were positively associated to intra-thalamic NAA/cre (r=0.4; p=0.006), however not to diabetes duration (p=0.5), severity of DSPN (p=0.7), or presence of pain (p=0.3). Individuals with the lowest thalamic volume had greatest loss of protective sensation (light touch using von Frey-like filaments, p=0.037) and highest pain tolerance to electric stimulation (tetanic stimulation, p=0.008) compared to individuals with the highest thalamic volume.Conclusions In this cohort with type 1 diabetes and severe DSPN, thalamic atrophy was present and associated with reduced NAA/cre, indicating thalamic structural loss and dysfunction. Thalamic atrophy was associated to reduced sensory function involving large fiber neuropathy and sensation to tetanic stimulation that may reflect synaptic transmission. This may ultimately contribute to the current understanding of the pathophysiology behind the perception changes evident in DSPN.
Keywords: Brain metabolites; Central nervous system; Diabetic neuropathy; Magnetic Resonance Spectroscopy; Peripheral nervous system; Thalamus